2009
DOI: 10.1590/s0103-84782009000500032
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de modelos para predição da energia metabolizável do milho para aves

Abstract: IIAvaliação de modelos para predição da energia metabolizável do milho para aves Evaluation of models to predict metabolizable energy of corn for chickens RESUMO C3 = 4021,5*MM; EMA n C4 = 4337,17*FDN; e EMA n C5 = 4371,[18][19][20][21][22][23][24][25][26]48*PB + 30,14*FDN + 24,40 O estudo foi realizado com o objetivo de avaliar modelos de predição do valor de energia metabolizável aparente corrigida (EMAn ABSTRACT A study was realized to validate models to predict apparent metabolizable energy (AMEn) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These authors also found that the accuracy of the equations cannot only be attributed to the coefficient of determination. Similarly, Oliveira and Warpechowski (2009) reported that most of the models have good predictive power for the data set in which they were derived; however, there are few studies comparing the behavior of prediction models in sets of independent data. Based on the results obtained, we can infer that variations in the chemical composition of corn can provide different values for AME and AMEn.…”
Section: Resultsmentioning
confidence: 99%
“…These authors also found that the accuracy of the equations cannot only be attributed to the coefficient of determination. Similarly, Oliveira and Warpechowski (2009) reported that most of the models have good predictive power for the data set in which they were derived; however, there are few studies comparing the behavior of prediction models in sets of independent data. Based on the results obtained, we can infer that variations in the chemical composition of corn can provide different values for AME and AMEn.…”
Section: Resultsmentioning
confidence: 99%